2015
DOI: 10.1007/s00330-015-3821-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided core-needle biopsy in thyroid nodules. A study of 676 consecutive cases with surgical correlation

Abstract: Thyroid core-needle biopsy (CNB) has high sensitivity and PPV. Pitfalls of CNB are rare. Pitfalls are due to cystic cancer, histological heterogeneity, and mistakes in analysis. CNB is a reliable, safe, and accurate method to approach thyroid nodules. CNB can be used primarily or after insufficient or indeterminate FNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 40 publications
0
39
0
2
Order By: Relevance
“…Based on these data, diagnostic surgery has been strongly recommended when ATL or TL are suspected clinically or on FNA [19,20]. CNB studies, however, have shown higher sensitivity, ranging from 80 to 100 %, and in most cases were diagnostic [21][22][23][24][25][26][27][28]. As such, several investigators have emphasized the importance of CNB in avoiding unnecessary diagnostic surgery, although the number of patients in their studies was small, with ten at the maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data, diagnostic surgery has been strongly recommended when ATL or TL are suspected clinically or on FNA [19,20]. CNB studies, however, have shown higher sensitivity, ranging from 80 to 100 %, and in most cases were diagnostic [21][22][23][24][25][26][27][28]. As such, several investigators have emphasized the importance of CNB in avoiding unnecessary diagnostic surgery, although the number of patients in their studies was small, with ten at the maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Both observers identified LTILs as having a full-thickness defect or ‘torn’ when contrast injected into the radiocarpal compartment extravasated into the midcarpal compartment or contrast injected into the midcarpal compartment extravasated into the radiocarpal compartment via the lunotriquetral interval; observers classified all other LTILs as ‘not torn’ [19]. LTIL injury status was evaluated using static fluoroscopic images and MR arthrograms (see Figs 3, 4, 5, and 6 for examples of full-thickness LTIL tears).…”
Section: Methodsmentioning
confidence: 99%
“…Diagnostic discrepancies between observers were resolved by consensus upon rigorous re-evaluation of all available scans prior to statistical analysis. Given that subregions of the LTIL lie oblique to the axial plane and that, at our institution, MR arthrograms are routinely acquired in the standard axial plane, we did not feel we could reliably localize the portion(s) of the LTIL that were torn [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Frozen sections are not useful in this context, demonstrating to be biased by a low diagnostic power, essentially due to the inconsistency of classical nuclear features in such methods. Some attempts have been made in order to reach higher diagnostic power in cases diagnosed as indeterminate by enlarging the amount of tissue sampled, and core needle biopsy has been used in this setting [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%